Modelamento de guia de onda ultracompacto de baixa perda baseado em cristal fotônico com configuração em espiral e serpentina - Renan Matheus Soares da Silva (2023)
The modeling of waveguides that require long interaction length is commonly demanded in the field of photonics for different applications. This requirement may require a reduction in the dimensions of the device, which depends on the waveguide compaction process depending on its length. To achieve this, it is common to implement curvatures in the waveguide. In photonic crystal (CF), high output loss is common when curvatures are implemented in the waveguide. This phenomenon is due to unwanted reflection, scattering and backpropagation. Therefore, the development of long waveguides in photonic crystals is uncommon due to the difficulty in implementing the curvatures in the channel. The objective of this work is the design of ultra- compact low-loss waveguides (<1%) with a length of approximately 1 cm, implemented in photonic crystal. The study is composed of a photonic crystal formed by silicon on the substrate and air cavities arranged in a triangular lattice, with light propagation at a wavelength of 1550 nm. The structures were generated through the Photonic Band Gap (PBG) using the Plane Wave Expansion (PWM) method, the cut-off of the waveguide using the Finite Difference Automode (Finite- Difference Eigenmode – FDE) and transmission calculations using the Finite- Difference Time-Domain (FDTD) method. Initially, the generation of photonic crystal structures is proposed, respecting parameters such as working wavelength, materials, cavities distribution, waveguide cut-off and calculated PBG. For these structures, the transmission profile of a straight waveguide is calculated and subsequently, with curvatures implemented. Based on these profiles, the device modeling process begins. Firstly, through supercavities in the curvatures to increase the average transmission of the waveguide. Subsequently, the study of the distance between parallel waveguides is presented, in order to avoid coupling losses. Two methods are presented for reducing the waveguide footprint through spiral and serpentine configuration based on the modeling results. A way of reducing the waveguide width will also be proposed. Final simulations prove the possibility of designing waveguides with approximately 1 cm in length and low loss (<1%) in photonic crystal, considering the construction requirements. Finally, using compression methods, ultra-compact waveguides were modeled in a spiral and serpentine configuration to obtain photonic crystals with dimensions of ~210x184 (μm) and ~255x188 (μm), respectively. This work directly contributes to new research involving applications that require devices formed by a long-length low-loss waveguide implemented in a photonic crystal, the need to couple two devices on a chip using waveguides with curvature and various applications, such as parametric amplifiers, components using dense wavelength multiplexing, optical regenerators and construction of real-time delay lines.